2014
DOI: 10.3844/ajessp.2014.148.156
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Speciation in Selected Agricultural Soils of Peninsular Malaysia

Abstract: Manganese speciation in selected agricultural soils of Peninsular Malaysia is discussed in this study. Manganese concentration in the Easily Leacheable and Ion Exchangeable (ELFE), Acid Reducible (AR), Organic Oxidizable (OO) and Resistant (RR) fractions of soils developed on weathered rocks, soils of mixed nature, alluvium and peat deposits are described. The total manganese concentration in soils developed on weathered rocks was found to be higher than that in soils of mixed nature, alluvium and peat deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Meanwhile, manganese concentration is also high in samples from several monitoring wells. The high levels of manganese in groundwater is also contributed by the criteria of the peat soil which enhanced manganese oxide accumulation (Jusop et al, 2014). The occurrence of rock weathering in peat soil areas enhances the manganese concentration in groundwater.…”
Section: Heavy Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, manganese concentration is also high in samples from several monitoring wells. The high levels of manganese in groundwater is also contributed by the criteria of the peat soil which enhanced manganese oxide accumulation (Jusop et al, 2014). The occurrence of rock weathering in peat soil areas enhances the manganese concentration in groundwater.…”
Section: Heavy Metalmentioning
confidence: 99%
“…However, manganese showed higher levels than the permissible level of 0.2 mg/L by MOH in raw water at several monitoring well stations. The high manganese content in groundwater is generally derived from rock weathering processes in peat soil, due to the resistance of manganese at topsoil surfaces (Jusop et al, 2014). Therefore, the groundwater sources in Banting, Kuala Langat showed influences from seawater in the groundwater bodies.…”
Section: Permissible Limit In Groundwatermentioning
confidence: 99%
“…Schulte and Kelling (1999) also reported higher Mn concentrations in acidic sandy soils in a previous study. Moreover , Habibah et al (2014) observed superfluous levels of Mn in acidic waterlogged soils low in organic matter. With the possibility of Mn being able to accumulate in various soil depths, the element also builds up in surface layers due to its placement by organic matter (Kabata-Pendias 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Manganese (Mn) is a heavy metal normally found in soils in the form of oxides/hydroxides (Habibah et al 2014) and also listed among iron, zinc, and copper to be a critical micronutrient required for appropriate plant growth (Vukasinovic et al 2015). Though Mn oxides commonly exist in the amorphous form, crystalline nature of the oxide has also been observed by some authors (Habibah et al 2014). Tashakor et al (2011) observed a strong attachment of cobalt (Co) to Mn oxides but opined that because Mn oxides are moderately Christian Kofi Anthonio and Huang Jing contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation